NADPH oxidases regulate endothelial inflammatory injury induced by PM2.5 via AKT/eNOS/NO axis. Issue 5 (28th October 2021) - Zou, Lingyue; Xiong, Lilin; Wu, Tianshu; Wei, Tingting; Liu, Na; Bai, Changcun; Huang, Xiaoquan; Hu, Yuanyuan; Xue, Yuying; Zhang, Ting; Tang, Meng
Abstract: Fine particulate matter (PM2.5 )‐induced detrimental cardiovascular effects have been widely concerned, especially for endothelial cells, which is the first barrier of the cardiovascular system. Among potential mechanisms involved, reactive oxidative species take up a crucial part. However, source of oxidative stress and its relationship with inflammatory response have been rarely studied in PM2.5 ‐induced endothelial injury. Here, as a key oxidase that catalyzes redox reactions, NADPH oxidase (NOX) was investigated. Human umbilical vein endothelial cells (EA.hy926) were exposed to Standard Reference Material 1648a of urban PM2.5 for 24 h, which resulted in NOX‐sourced oxidative stress, endothelial dysfunction, and inflammation induction. These are manifested by the up‐regulation of NOX, increase of superoxide anion and hydrogen peroxide, elevated endothelin‐1 (ET‐1) and asymmetric dimethylarginine (ADMA) level, reduced nitric oxide (NO) production, and down‐regulation of phosphorylation of endothelial NO synthase (eNOS) with increased levels of inducible NO synthase, as well as the imbalance between tissue‐type plasminogen activator (tPA) and plasminogen activator inhibitor 1 (PAI‐1), and changes in the levels of pro‐inflammatory and anti‐inflammatory factors. However, administration of NOX1/4 inhibitor GKT137831 alleviated PM2.5 ‐induced elevated endothelial dysfunction biomarkers (NO, ET‐1, ADMA, iNOS, and tPA/PAI‐1), inflammatory factors (IL‐1β, IL‐10, and IL‐18), and adhesion molecules (ICAM‐1, VCAM‐1, and P‐selectin) and also passivated NOX‐dependent AKT and eNOS phosphorylation that involved in endothelial activation. In summary, PM2.5 ‐induced NOX up‐regulation is the source of ROS in EA.hy926, which activated AKT/eNOS/NO signal response leading to endothelial dysfunction and inflammatory damage in EA.hy926 cells. Abstract : This study selected low levels of PM2.5 exposure doses to explore the early oxidative occurrence and molecular changes in endothelial injury. We mainly evaluated the role of NAPDH oxidase (NOX) in the PM2.5 ‐induced inflammatory endothelial damage. ROS produced by NOXs and uncoupled eNOS acted as initiators of inflammatory response, aggravating the endothelial dysfunction. In conclusion, with the application of NOX‐specific antioxidants in PM2.5 ‐mediated endothelial injury, we hope to identify key initial targets and provide new insights for the risk assessment.